2003
DOI: 10.1002/bmc.322
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of four bufadienolides in human liver by high‐performance liquid chromatography

Abstract: A high-performance liquid chromatographic method for the simultaneous quantitation of four bufadienolides-cinobufotalin, bufalin, cinobufagin and resibufogenin-in human liver was investigated. The procedure involved solid phase extraction of human liver with an Oasis HLB cartridge coupled with reversed-phase HPLC and photodiode array detection. Recoveries obtained from spiked liver for the bufadienolides were better than 70%. The linearity was studied up to 1.2 mg/kg and the detection limits of the method were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 6 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…Chan Su is another single herb with anticancer activity. Bufadienolides, including bufalin, cinobufagin, resibufogenin and telocinobufagin, are the major active constituents derived from Chan Su (32). Chan Su and its constituents have been reported to be able to suppress cellular growth and promote apoptosis in leukaemia, liver, lung and prostate cancers (19).…”
Section: Curcuma Longamentioning
confidence: 99%
“…Chan Su is another single herb with anticancer activity. Bufadienolides, including bufalin, cinobufagin, resibufogenin and telocinobufagin, are the major active constituents derived from Chan Su (32). Chan Su and its constituents have been reported to be able to suppress cellular growth and promote apoptosis in leukaemia, liver, lung and prostate cancers (19).…”
Section: Curcuma Longamentioning
confidence: 99%
“…These two active compounds were identified as resibufogenin and cinobufagin, which are members of the bufadienolide family. Bufadienolides, including resibufogenin, cinobufagin, bufalin, bufotalin and arenobufagin, are a type of steroidal cardiac glycosides (17) that exhibit a variety of biological effects, including cardiotonic, anesthetic and antineoplastic activities (18). Bufalin, as a major active compound of bufadienolide, has been demonstrated to possess significant anti-proliferative activities and apoptosis-inducing effects on human leukaemia, liver, prostatic, endometrial and ovarian cancer cells (19,20).…”
Section: Effects Of Cinobufagin On the Expression Of Apoptosis-relatementioning
confidence: 99%
“…Recent literature revealed that several methods have been used to determine bufadienolides in toad venom [8][9][10], in traditional Chinese medicines formula [11][12][13] and in human liver [14]. In all of these reports, reversedphase HPLC/UV was used as the quantitative determination technique.…”
Section: Introductionmentioning
confidence: 99%